2018
DOI: 10.14440/jbm.2018.256
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned contextual fear memory to assess natural forgetting and cognitive enhancement in rats

Abstract: Aversively established contextual fear memory manifests itself in robust freezing behavior, often lasting several weeks or months. Therefore, this approach is amenable to investigate the underlying neural circuitries by lesion or inactivation of specific brain regions or to test efficacy of substances that disrupt either the ability to acquire the association or to retrieve memories. In contrast, investigation of memory enhancement using this technique is time intensive since the non-treated control group natu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…To assess associative memory, they were also tested for contextual/cued fear conditioning. Fear conditioning is a classical pavlovian model to assess associative memory for the pairing of a neutral CS (tone-cue) and the context with an aversive US (electric foot shock) 30 . Once this pairing is acquired, either the context or the tone-cue alone induces the conditioned reaction, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess associative memory, they were also tested for contextual/cued fear conditioning. Fear conditioning is a classical pavlovian model to assess associative memory for the pairing of a neutral CS (tone-cue) and the context with an aversive US (electric foot shock) 30 . Once this pairing is acquired, either the context or the tone-cue alone induces the conditioned reaction, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The fear-conditioning test assess associative memory 30 and was performed as previously described 49 . Briefly, the conditioning trial for contextual and cued fear conditioning consisted of a 5-min exploration period followed by three conditioned stimulus-unconditioned stimulus pairings (CS-US), each separated by a 1 min intertrial interval (US: 1 mA foot shock intensity, 1 s duration; CS: 80 db white noise, 20 s duration; US was delivered during the last seconds of CS presentation).…”
Section: Methodsmentioning
confidence: 99%
“…It is important to note that most neurobiological studies employ simple temporal pairings of CS and US to produce fear conditioning [ 51 , 52 ]. Previous studies have shown that fear conditioning can be rapidly instilled in animals, even after a single conditioning trial, and is usually maintained for long periods [ 14 , 53 ]. This study observed that by increasing the number of CS-US pairings, the animals exhibited higher freezing responses, indicating a comparable level of learning during the training.…”
Section: Discussionmentioning
confidence: 99%